UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN THINK-PAIR-SHARE PADA SISWA KELAS VII A DI SMP MUHAMMADIYAH SALAM KABUPATEN MAGELANG - Meta Galuh Septiardi; AA Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
The purpose of this study was to improve liveliness and mathematics achievement in cooperative students of class VII A SMP Muhammadiyah Salam Magelang with cooperative learning TPS (Think Pair Share). This research is Classroom Action Research (CAR). The subjects in this study were students of class VII A which is 15 students who comprised 10 male students and 5 female students. Research findings indicate that the liveliness and increase math achievement. This can be shown by an increase in the average yield percentage of student learning liveliness based on the observation sheet for each cycle is the first cycle of student liveliness and 63.33% for the second cycle was 88.83%. While the average value interpretation of students' mathematics learning increased from an average initial value of the average of 46.33 to 55.67 in the first cycle and the second cycle to 84,67.